Developing mHealth remote ronitoring rechnology for attention deficit hyperactivity disorder: a qualitative study eliciting user priorities and needs - Simons, Lucy; Valentine, Althea Z.; Falconer, Caroline J.; Groom, Madeleine; Daley, David; Craven, Michael P.; Young, Zoe; Hall, Charlotte; Hollis, Chris (JMIR Publications, 2016)
Background: Guidelines in the United Kingdom recommend that medication titration for attention deficit hyperactivity disorder (ADHD) should be completed within 4-6 weeks and include regular reviews. However, most clinicians think that weekly clinic contact is infeasible, and audits have shown that this timeline is rarely achieved. Thus, a more effective monitoring and review system is needed; remote monitoring technology (RMT) may be one way to improve current practice. However, little is known about whether patients with ADHD, their families, and clinicians would be interested in using RMT. Objective: To explore patients’, parents’, and health care professionals’ views and attitudes toward using digital technology for remote monitoring during titration for ADHD. Methods: This was a qualitative study, and data were collected through 11 focus groups with adults and young people with ADHD, parents of children with ADHD, and health care professionals (N=59). Results: All participant groups were positive about using RMT in the treatment of ADHD, but they were also aware of barriers to its use, especially around access to technology and integrating RMT into clinical care. They identified that RMT had the most potential for use in the ongoing management and support of ADHD, rather than during the distinct titration period. Participants identified features of RMT that could improve the quality of consultations and support greater self-management. Conclusions: RMT has the potential to augment support and care for ADHD, but it needs to go beyond the titration period and offer more to patients and families than monitoring through outcome measures. Developing and evaluating an mHealth app that incorporates the key features identified by end users is required.